Penerapan Model Bisnis Canvas pada POKLAHSAR di Kronjo, Kab. Tangerang [Application of the Business Model Canvas in POKLAHSAR, Kronjo, Tangerang Regency] - Setiyowati, Harlis; Meidiyustiani, Rinny; Kusumaningsih, Dewi; Akbariani, Nurhaliza Vania; Maulana, Irfan; Aryanto, Puput (Indonesia Berdaya, 2026)
Abstract. Small-scale fish processing activities in Kronjo District, Tangerang Regency, play a significant role in supporting the coastal community’s economy; however, they still face limitations in structured and sustainable business management. Most fish processors operate traditional businesses without a clear understanding of their business models, resulting in underutilized value-added potential. This community service activity aims to apply the Business Model Canvas (BMC) as a mentoring tool to enhance managerial capacity and business understanding among fish processors in Kronjo District. The method employed was a descriptive qualitative approach within a community engagement framework, using field observations, interviews, and focus group discussions. The results indicate that the implementation of the Business Model Canvas improved partners’ understanding of their business structure, particularly in identifying customer segments, formulating value propositions, and recognizing the relationship between cost structures and revenue streams. The application of BMC also encouraged a shift in mindset from a production-oriented approach to more structured and sustainable business management. This activity concludes that the Business Model Canvas is an effective and practical tool for community service programs aimed at strengthening small-scale fish processing businesses and enhancing the welfare of coastal communities. Abstrak. Kegiatan pengolahan ikan skala kecil di Kecamatan Kronjo, Kabupaten Tangerang, memiliki peran penting dalam menopang perekonomian masyarakat pesisir, namun masih menghadapi keterbatasan dalam pengelolaan usaha yang terstruktur dan berkelanjutan. Sebagian besar pelaku usaha menjalankan bisnis secara tradisional tanpa pemahaman yang memadai mengenai model bisnis, sehingga potensi nilai tambah produk belum dimanfaatkan secara optimal. Kegiatan ini bertujuan untuk menerapkan Business Model Canvas (BMC) sebagai alat pendampingan guna meningkatkan pemahaman dan kapasitas manajerial pengolah ikan di Kecamatan Kronjo. Metode yang digunakan adalah pendekatan deskriptif kualitatif berbasis pengabdian kepada masyarakat melalui observasi lapangan, wawancara, dan diskusi kelompok terarah. Hasil kegiatan menunjukkan bahwa penerapan Business Model Canvas membantu mitra memahami struktur bisnis secara lebih komprehensif, khususnya dalam mengidentifikasi segmen pelanggan, merumuskan proposisi nilai, serta memahami hubungan antara biaya dan pendapatan usaha. Penerapan BMC juga mendorong perubahan pola pikir mitra dari orientasi produksi menuju pengelolaan usaha yang lebih terarah dan berkelanjutan. Kegiatan ini menyimpulkan bahwa Business Model Canvas merupakan alat yang efektif dan aplikatif dalam program pengabdian kepada masyarakat untuk mendukung penguatan usaha pengolahan ikan dan peningkatan kesejahteraan masyarakat pesisir.